Modelo de tempo de falha acelerado com fração de cura : uma abordagem unificada - Guedes, Alysson Lívio Vasconcelos (2011)
In this work we study the accelerated failure-time generalized Gamma regression models with a unified approach. The models attempt to estimate simultaneously the effects of covariates on the acceleration/deceleration of the timing of a given event and the surviving fraction. The method is implemented in the free statistical software R. Finally the model is applied to a real dataset referring to the time until the return of the disease in patients diagnosed with breast cancer